Training Field Size Matters: Impacts On Decision-Making Skills In Football - Tesema (Ph.D), Gashaw; Desalegn, Alemnew; Gedefaw (Ph.D), Haileyesus (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
The study aimed to compare the impact of the small-sided versus large-sided game approach on the decision-making skills of U-17 male youth football trainees. A total of 52 players from two youth teams in Bahir Dar, Ethiopia, participated in a 10-week intervention. The study used experimental design with two comparative groups: the small field size trainee group, which trained on a 46m × 25m pitch using 6v6 games; and the large field size trainee group, which trained on an 80m × 40m pitch using 11v11 games. Both groups participated in two 70-minute sessions per week, focusing on decision-making in four key areas: passing, receiving, dribbling, and shooting. The study employed pre-and post-tests to assess decision-making skills, with data collected through video recordings and analyzed using decision-making indices. The data were analyzed using independent-sample t-tests to compare pre-test decision-making indices between the two groups. In the pre-test, both groups were comparable across all decision-making variables (p > 0.05), indicating no significant baseline differences. Following the 10-week training intervention, both groups demonstrated improvements in decision-making. However, the small-field size training group showed a significant improvement in shooting decision-making, with a decision-making index of 90.9% compared to 63.63% in the large-field size training group (p = 0.020). No significant differences were found between the groups in passing, receiving, or dribbling decision-making. The findings confirmed that the smaller, more intense environment of small-sided games may better facilitate rapid decision-making under pressure, especially in shooting situations. Based on the result of the study and the firm support from previous literature, it is concluded that the cognitive benefits of small-sided games, provide more frequent, high-intensity interactions that promote quick decision-making. In contrast, large-sided games offer more time and space, potentially reducing the urgency for quick decisions, particularly in actions like shooting. This study underscores the value of small-sided games in enhancing decision-making skills in youth football, particularly under pressure, and recommends that a balanced training approach incorporating both small and large-sided games may optimize player development